2021
DOI: 10.3390/pharmaceutics13101606
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis and Physicochemical Characterization of Previously Unreported Praziquantel Solvates with 2-Pyrrolidone and Acetic Acid

Abstract: Two new solvates of the widely used anthelminthic Praziquantel (PZQ) were obtained through mechanochemical screening with different liquid additives. Specifically, 2-pyrrolidone and acetic acid gave solvates with 1:1 stoichiometry (PZQ-AA and PZQ-2P, respectively). A wide-ranging characterization of the new solid forms was carried out by means of powder X-ray diffraction, differential scanning calorimetry, FT-IR, solid-state NMR and biopharmaceutical analyses (solubility and intrinsic dissolution studies). Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
(97 reference statements)
1
15
0
Order By: Relevance
“…For the experiments using acetic acid as solvent, the acetic acid solvate (PZQ-AA) was obtained in all experimental conditions, confirmed by comparison with the simulated powder pattern DAJCEA 21 (Supporting Information, Figure S2). PZQ-AA was first obtained by Zanolla et al via liquidassisted grinding using a vibrational mill.…”
Section: Polymorphic Outcome From Single Solventssupporting
confidence: 53%
See 2 more Smart Citations
“…For the experiments using acetic acid as solvent, the acetic acid solvate (PZQ-AA) was obtained in all experimental conditions, confirmed by comparison with the simulated powder pattern DAJCEA 21 (Supporting Information, Figure S2). PZQ-AA was first obtained by Zanolla et al via liquidassisted grinding using a vibrational mill.…”
Section: Polymorphic Outcome From Single Solventssupporting
confidence: 53%
“…The DSC curve of PZQ-AA (blue curve) is shown in Figure , characterized by a single endothermic event at 72.19 °C. Zanolla et al reported this event (peak at 72.26 °C) as the melting point of PZQ-AA, also confirmed by hot-stage microscopy . Before starting thermal decomposition, a mass loss of 15.60% up to 200 °C is observed in TGA.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, it is very important to improve the water solubility of praziquantel to reduce the dosage of praziquantel for better development of pediatric drug use and to reduce the probability of drug resistance and adverse reactions, as well as to protect global public health security [ 7 ].The solubility of praziquantel can be improved by preparing praziquantel solid dispersions, lipid nanoparticles or cyclodextrin inclusion compounds, but are limited by instability during preparation or storage. Considering the advantages of cocrystal technology in improving the physical and chemical properties of compounds, many researchers have carried out related studies on PRA [ 8 , 9 , 10 , 11 ]. At present, 27 cocrystals of PRA have been reported in the Cambridge Structural Database (CSD), and based on the analysis of their structural information, the cocrystal coformers (CCFs) of PRA were all carboxylic acid compounds or compounds with polyphenol hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…PZQ has two known hydrates, a monohydrate (MH) [ 15 ] and a hemihydrate (HH) [ 16 ], and a hemihydrate has been reported for every drug enantiomer [ 17 , 18 ]. Other solid forms of PZQ, obtained as solvates [ 19 ], cocrystals [ 20 ], a cyclodextrin complex [ 21 ], and solid-solid dispersions [ 22 , 23 ] widen the landscape of the PZQ solid forms.…”
Section: Introductionmentioning
confidence: 99%